2012
DOI: 10.1159/000338175
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Comorbidities for Prediction of Progression-Free Survival in Patients with Metastatic Renal Cell Carcinoma Treated with Sorafenib

Abstract: Background/Aims: The purpose of the present study was to determine the relationship between iatrogenic arterial hypertension or baseline cardiovascular comorbidities and outcomes in metastatic renal cell cancer (mRCC) patients treated with sorafenib. Methods: The study included 148 mRCC patients treated with sorafenib, 63 patients (43%) had preexisting hypertension, 18 patients (12%) coronary artery disease, and 15 patients (10%) mild heart failure. Resting blood pressure (BP) was monitored by clinic and home … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Patients with any grade of HTN while on treatment, according to CTCAE v3.0 (15 of 39 evaluable patients), lived longer than those without HTN, with a median overall survival of 18.2 months (95% CI 4.5-35.7) and 4.5 months (95% CI 2.4-7.3), respectively (P ¼ 0.0165). Szmit et al 38 39 showed that patients with mean increases in diastolic BP (Ä dBP) X15 mm Hg (n ¼ 18) per ambulatory BP monitoring performed on cycle 1 day 15 had a higher objective response rate than those with Ä dBP o15 mm Hg (n ¼ 36; 61 versus 53%). These results indicate that HTN is a biomarker of tumor response and improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with any grade of HTN while on treatment, according to CTCAE v3.0 (15 of 39 evaluable patients), lived longer than those without HTN, with a median overall survival of 18.2 months (95% CI 4.5-35.7) and 4.5 months (95% CI 2.4-7.3), respectively (P ¼ 0.0165). Szmit et al 38 39 showed that patients with mean increases in diastolic BP (Ä dBP) X15 mm Hg (n ¼ 18) per ambulatory BP monitoring performed on cycle 1 day 15 had a higher objective response rate than those with Ä dBP o15 mm Hg (n ¼ 36; 61 versus 53%). These results indicate that HTN is a biomarker of tumor response and improved survival.…”
Section: Discussionmentioning
confidence: 99%
“…Although the reason for this discrepancy is unclear, the optimal drug concentration might be changed due to decrease in renal or liver function in elderly patients; therefore, there is a possibility that a lower than usual dose might achieve a sufficient anti-tumour effect in this patient population. The fact that the frequency of hypertension, a predictive factor of TKI treatment, 2123 was higher in ≥75-year-old patients reflected these physical status specific for elderly patients. As for the frequency of AEs during sorafenib treatment, hypertension and decrease in appetite were higher in the ≥75-year group, but there was no significant difference for other AEs (Table 3).…”
Section: Discussionmentioning
confidence: 97%
“…Hypertension related to sunitinib or sorafenib treatment in patients with mRCC is associated with a better response and prolonged OS (Rixe et al 2007; Szmit et al 2012a, b). In a retrospective analysis of over 500 patients those who developed hypertension during sunitinib treatment had significantly longer PFS and OS compared to patients not developing hypertension (Rini et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension induced by sorafenib is also a factor for early response evaluation (Szmit et al 2012b). …”
Section: Introductionmentioning
confidence: 99%